Machiavelli Tendencies of the Officials of State Border Communicative Competence - Oliynyk, V. V. (Psychological Prospects Journal, 2011)
The article is dedicated to the theoretic empirical research of the officials of state border service communicative competence. The level of machiavelli characteristics manifestation is defined. On the basis of obtained results reference materials concerning improvement of the officials of state border service communicative competence are presented to the military units psychologists.
Keywords: communication communicative competence machiavellism border guards